АНЖИР ПАРВОНАСИ (CHOREUTIS NEMORANA HB.)НИНГ БИОЛОГИЯСИ (Scientific journal of the Fergana State University, 2023)
The article to the biological peculiarities of the Choreutis nemorana Hb. in the Fergana valley is devoted. It is established, that the Choreutis nemorana Hb. Is widespread species for the season develops five generation